Cognitive Emotion Regulation among Visually Impaired Young Adults: Insights from an Indian Context - Smriti Singh; Shalini Agarwal; Rishi Dikshit (The Bioscan, 2025)
This study examined cognitive emotion regulation strategies among visually impaired young adults, who face significant emotional and psychological challenges due to their disability. The aim was to investigate patterns of emotion regulation in the currently underexamined population of individuals with VI, as these are known to experience difficulties with emotion regulation compared to their sighted peers. Sixty-six visually impaired college students in the age of 20 to 30 years were assessed in a cross-sectional study using standard questionnaire for cognitive emotion regulation strategies in Lucknow. The study revealed a significant gender difference, with female scoring higher on maladaptive strategies like self-blame, catastrophizing, and blaming others. Differences in family type for only Positive Refocusing, significant differences emerged between joint and nuclear family types. The study underscores the need for targeted strategies to improve emotion regulation skills in young adults with VI, focusing on gender-specific patterns and leveraging family support.